Diurnal variation in serum levels of cartilage oligomeric matrix protein in patients with knee osteoarthritis or rheumatoid arthritis. Issue 11 (17th May 2006) - Andersson, M L E; Petersson, I F; Karlsson, K E; Jonsson, E N; Månsson, B; Heinegård, D; Saxne, T
Abstract : Objective: To monitor changes in serum concentrations of cartilage oligomeric matrix protein (COMP) during a 24-h period to determine any diurnal variation, and to estimate the half life of COMP in the circulation in patients with symptomatic knee osteoarthritis and in those with rheumatoid arthritis. Methods: Serum samples were drawn every 4 h (7 samples/patient over 24 h) in 10 patients with knee osteoarthritis and 14 patients with rheumatoid arthritis. Osteoarthritis was defined radiographically and clinically (American College of Rheumatology (ACR) criteria) and rheumatoid arthritis according to the 1987 ACR criteria. Serum COMP was measured by sandwich ELISA. A statistical model for the diurnal variation in the COMP levels was developed using the computer program NONMEM. Results: No considerable changes in COMP levels were observed during the day between 08:00 and 21:00 in either group. A significant decrease in serum COMP was apparent during bed rest at night, reaching the lowest levels between 04:00 and 05:00 (p<0.03 or better v all other time points) in patients with osteoarthritis and in those with rheumatoid arthritis. From the rate of decreasing serum COMP levels, a putative half life of COMP in the circulation was estimated to be 7.4 h. Conclusion: During normal daytime activities, serum COMP levels are constant. The decrease during the night indicates a rapid elimination of COMP once it has reached the circulation. The stable COMP levels during the day suggest that it is not necessary to further standardise the time of serum sampling in clinical practice.